A Functional Genomics Approach for Characterizing the Role of Six Transcription Factors in Muscle Development - Chu, Alphonse (Université d'Ottawa / University of Ottawa, 2012)
Proper development of skeletal muscle occurs through a highly complex process where activation and repression of genes are essential. Control of this process is regulated by timely and spatial expression of specific transcription factors (TFs). Six1 and Six4 are homeodomain TFs known to be essential for skeletal muscle development in mice. Using the C2C12 cell line, a model for skeletal muscle differentiation, I used a functional genomics approach, employing siRNA specific to both these TFs, to characterize their role in skeletal myogenesis. To identify the genes that are regulated by both these TFs, gene expression profiling by microarray of cells treated with siRNA against Six1 and/or Six4 was performed. The knock-down of these TFs caused lower expression of markers of terminal differentiation genes in addition to an impairment of myoblast fusion and differentiation. Interestingly, transcript profiling of cells treated with siRNA against myogenin revealed that several of the Six1 and Six4 target genes are also regulated by myogenin. Through a combination of bioinformatic analyses it was also found that specific knock-down of Six4 causes an up-regulation of genes involved in mitosis and the cell cycle. In summary, these results show that Six1 and Six4 can both independently regulate different genes, but can also cooperate together with other TFs where they play an important role in the proper regulation of skeletal myogenesis.
Keywords: Myogenesis; Systems Biology; Microarray; Six Transcription Factors; ChIP-on-Chip; Functional Genomics; Clustering; Genome Wide Transcript Profiling; Promoter Analysis; Gene Function Annotation; C2C12; Differentiation; RNA Interference